A pharmacy asthma service achieves a change in patient responses from increased awareness to taking responsibility for their asthma. (4th July 2014) - Naik-Panvelkar, Pradnya; Saini, Bandana; LeMay, Kate S; Emmerton, Lynne M; Stewart, Kay; Burton, Deborah L; Bosnic-Anticevich, Sinthia Z; Krass, Ines; Smith, Lorraine D; Armour, Carol L
Abstract: Objectives: If novel health services are to be implemented and sustained in practice, the perceptions and views of patients form a critical part of their evaluation. The aims of this study were to explore patient's perceptions and experiences with a pharmacy asthma service and to investigate if there was a change over time. Methods: Interviews and focus groups were conducted with patients participating in the asthma service at three time points. Data were transcribed verbatim and thematically analyzed using a framework approach. Key findings: The service led to an enhanced awareness and understanding of asthma, changes in participants' beliefs and attitudes towards asthma management, changes in asthma-related health behaviours and improved self-efficacy. Participants were very positive about the service and the role of the pharmacist in asthma management. There was a shift in participant perceptions and views, from being at an abstract level in those who had completed just one visit of the service to a more experiential level in those who had experienced the entire comprehensive asthma service. Conclusions: A sustained experience/multiple visits in a service may lead to more concrete changes in patient perceptions of severity, beliefs, health behaviours and enhanced self-efficacy and control. The study highlights a need for such asthma services in the community.